Methods and Outcomes for the Remediation of Clinical Reasoning - Guerrasio, Jeannette (J Gen Intern Med, 2014)
INTRODUCTION: There is no widely accepted structured, evidence based strategy for the remediation of clinical reasoning skills. AIM: To assess the effectiveness of a standardized clinical reasoning remediation plan for medical learners at various stages of training. SETTING: Learners enrolled in the University of Colorado School of Medicine Remediation Program. PROGRAM DESCRIPTION: From 2006 to 2012, the learner remediation program received 151 referrals. Referrals were made by medical student clerkship directors, residency and fellowship program directors, and through self-referrals. Each learner’s deficiencies were identified using a standardized assessment process; 53 were noted to have clinical reasoning deficits. The authors developed and implemented a ten-step clinical reasoning remediation plan for each of these individuals, whose subsequent performance was independently assessed by unbiased faculty and senior trainees. Participant demographics, faculty time invested, and learner outcomes were tracked. PROGRAM EVALUATION: Prevalence of clinical reasoning deficits did not differ by level of training of the remediating individual (p = 0.49). Overall, the mean amount of faculty time required for remediation was 29.6 h (SD = 29.3), with a median of 18 h (IQR 5–39) and a range of 2–100 h. Fifty-one of the 53 (96 %) passed the post remediation reassessment. Thirty-eight (72 %) learners either graduated from their original program or continue to practice in good standing. Four (8 %) additional residents who were placed on probation and five (9 %) who transferred to another program have since graduated. DISCUSSION: The ten-step remediation plan proved to be successful for the majority of learners struggling with clinical reasoning based on reassessment and limited subsequent educational outcomes. Next steps include implementing the program at other institutions to assess generalizability and tracking long-term outcomes on clinical care.